Analysis of Income and Contribution to Household Income of Fried Fried Businesses in Kendari City - Sudarmo, Hadi; Iswandi, Raden Marsuki; Purwanti, Rahayu Endah; Nafilawati, Wa Ode (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2023)
In March 2022, there will be a national shortage of cooking oil. The price of cooking oil in Southeast Sulawesi at that time reached IDR 70,000 per liter, the highest in Indonesia. This has a big impact on households and fried food businesses as MSMEs because cooking oil is a daily necessity. Cooking oil is one of the main requirements for the sustainability of a fried food business, so without its use, the business will not run or close. This research aims to analyze the income and contribution to household income of fried food businesses in Kendari City. The location of the research was in Kendari City in Kiambu District (Jalan H.E.A. Mokodompit), Baruga District (along Jalan Jenderal A. Yani and Jalan Poros Halu Oleo Airport). The research results show that the average income of fried food businesses in Kendari City reaches IDR 17,837,236 per month. The highest income was obtained from the fried food business located on Jalan Ahmad Yani (Haluoleo Airport Axis) reaching IDR 26,377,042 per month, while the one located in front of the UHO Campus was IDR 9,297,431 per month. Analysis of the average income contribution reached 57% and the highest is located in front of the UHO campus at 64%, while the lowest is located in Ahmad Yani (Haluoleo Airport Axis) reaching 51%.